Method for preparing nano-copper particles from eucommia ulmoides extract and application of nano-copper particles in catalytic reduction reaction

By using Eucommia ulmoide extract as a reducing agent to prepare nanocopper particles in an aqueous environment, the problems of uneven particle size, easy agglomeration and high cost in the prior art are solved, and low-cost, green and environmentally friendly nanocopper particles are prepared, with good dispersion performance and catalytic efficiency.

CN119549733APending Publication Date: 2025-03-04YANGZHOU UNIV

Patent Information

Application Number
CN202411789032.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems such as uneven particle size, easy agglomeration, high cost, harmful to the human body and the environment, and complex wastewater treatment when preparing nanocopper particles.

Method used

The extract of Eucommia ulmoides is used as a reducing agent, and nanocopper particles are generated through chemical reaction with divalent copper salt solution in an aqueous environment. It is purified by magnetic stirring, dialysis and centrifugal separation to obtain nanocopper particles with good dispersion performance and low cost.

Benefits of technology

It has achieved the preparation of nano-copper particles with uniform particle size and good dispersion performance, which has reduced the cost of use, and is environmentally friendly in the process, so that the residue after the reaction is harmless to the environment and the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549733A_ABST
    Figure CN119549733A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nano-copper particles from eucommia ulmoides extract and application of the nano-copper particles in a catalytic reduction reaction in the technical field of metal nano-materials, the eucommia ulmoides extract is adopted as a reducing agent, a bivalent copper salt solution is added, a reaction can be carried out in a water phase, and the nano-copper particles are generated. The raw materials are cheap and easy to obtain, the reaction conditions are easy to control, the process is simple, and the prepared nano-copper particles have good dispersity and show a good catalytic effect in the aspect of catalytic reduction of organic dye and nitrophenol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal nanomaterials, and in particular to a low-cost green and environmentally friendly method for preparing ultra-small-size nano copper particles by aqueous phase reduction using eucommia extract as a reducing agent. Background Art

[0002] Nano copper particles (Cu NPs) have active chemical properties. Due to their ultra-small particle size and large specific surface area, they are more active than ordinary copper and are more likely to undergo chemical reactions. This active chemical property makes nano copper more efficient in catalytic reactions. However, due to their high surface energy, metal nanoparticles will aggregate to form larger particles, thereby losing their catalytic activity. Therefore, solving the agglomeration problem of nano copper particles has become one of the keys to their application.

[0003] Eucommia ulmoides is widely distributed in Sichuan, Yunnan, Guizhou and other places in my country and is a relatively common medicinal material. Eucommia ulmoides extract contains many secondary metabolites with reducing properties, such as chlorogenic acid, flavonoids and terpenes, which act as reducing agents in the preparation of nanocopper.

[0004] There are many methods for preparing nano copper particles, mainly physical methods and chemical methods. The physical method mainly prepares ordinary copper materials into nanoparticles through physical means such as mechanical grinding, ball milling, electron beam evaporation, and template method. However, these methods often have the disadvantages of uneven particle size, easy agglomeration, and high cost. The chemical method mainly reduces organic or inorganic compounds into nano copper through chemical reactions, such as chemical reduction, electrochemical method, solvent thermal method, sol-gel method, microemulsion method, gas phase method, organic precursor thermal decomposition method, etc. Among them, some methods use reducing agents with obvious health hazards, flammability, explosiveness, and corrosiveness, such as borohydride, hydrazine hydrate, sodium hypophosphite, etc. (Publication No. CN101607317A). These reducing agents not only have an impact on the human body and the environment, but also after the reaction is completed, the treatment of the reaction residue is also more troublesome. In addition, some preparation methods require the addition of multiple surface modifiers, such as dialkyl phosphoric acid or its salt, alkyl xanthic acid or its salt, dialkyl dithiophosphoric acid or its salt, dialkyl amino dithiocarboxylic acid or its salt, etc. (Publication No. CN101259531A), which not only makes the preparation process more complicated, but also increases the preparation cost; some preparation methods require N 2 protection (publication number CN101890506A), which increases the process cost; some preparation methods produce nano copper particles with a larger particle size, averaging about 60 nm (publication number CN105945302A).

[0005] Carmine and methylene blue, as typical representatives of azo dyes and thiophene derivatives respectively, will pose a direct threat to human health if they are released directly into the environment without proper treatment, and may cause a variety of adverse reactions and even diseases. It is also worth noting that nitrophenol compounds, as common pollutants in wastewater, have three structural isomeric forms: ortho, meta and para, and most of them are toxic. Once they come into direct contact with the human body, they may bring extremely serious health consequences.

[0006] Bulti Pramanick (Inorganic Chemistry Communications Volume 161, March 2024, 112040) used Cu-Ag composite nanomaterials to catalyze the reduction of 4-NP, and the catalytic kinetic constant was 7.79×10 -3 s −1 However, the addition of precious metal Ag increases the cost and has low industrial value.

[0007] At present, the liquid phase reduction method still has problems such as serious pollution of reaction residues, high energy consumption, high cost, complex subsequent treatment steps, lack of product stability, and low efficiency in treating organic dyes in wastewater. Therefore, it is very necessary to develop a low-cost, green and environmentally friendly method for preparing ultra-small nano-copper particles. Summary of the invention

[0008] The purpose of the present invention is to overcome the defects in the prior art and provide a method for preparing nano copper particles from eucommia extract. The eucommia extract is used as a reducing agent to generate nano copper particles through a chemical reaction with a divalent copper salt solution in an aqueous environment. The raw material cost is low, the prepared nano copper particles have good dispersibility, the catalytic efficiency for organic dyes and nitrophenols is high and the dosage is low, thereby reducing the use cost.

[0009] The object of the present invention is achieved in this way: a method for preparing nano copper particles from an eucommia extract comprises the following steps: dissolving an eucommia extract in water to form an aqueous solution, heating the aqueous solution to 70-80°C, and magnetically stirring the aqueous solution until it is fully mixed, and slowly adding a divalent copper salt solution to the solution while maintaining stirring until the solution reaches a stable state, and continuously reacting for 6-8 hours to reduce copper ions to obtain a yellow-brown aqueous solution containing nano copper particles; and then dialyzing the solution to remove impurities, further purifying it by centrifugal separation, taking the supernatant, and finally obtaining a pure nano copper aqueous solution.

[0010] When the present invention is working, the eucommia extract is used as a reducing agent, a divalent copper salt solution is added thereto, and nano copper particles are generated through chemical reactions in an aqueous environment. The raw material cost is low, the energy consumption is low, and the entire production process is green and environmentally friendly. The residue after the reaction is almost harmless to the environment and human body.

[0011] Furthermore, the mass ratio of the Eucommia ulmoides extract to the copper solution is (1-5):1.

[0012] Furthermore, the solution concentration of the Eucommia ulmoides extract is 0.04 g / mL~0.1 g / mL.

[0013] Furthermore, the divalent copper salt solution is a copper chloride solution, and the concentration of the copper chloride solution is 0.01 g / mL to 0.02 g / mL.

[0014] Furthermore, the divalent copper salt solution is added slowly through a constant pressure funnel and kept away from light.

[0015] Furthermore, the molecular weight cutoff of the dialysis bag used in the dialysis treatment is greater than 300, and the dialysis time is 6 to 12 hours.

[0016] Furthermore, the rotation speed of the centrifugal separation is 7000-8000 rpm, and the centrifugal time is 10-15 min.

[0017] The present invention also provides an application of the ultrafine nano copper particles obtained according to the preparation method as a catalyst in a catalytic reduction reaction, which is mainly used for catalytic reduction of organic dyes and nitrophenols.

[0018] Compared with the method of preparing ultra-small-size nano-copper particles using aconitic acid as a reducing agent as described in the patent specification of patent publication number CN109807351A, the present invention has the following advantages: (1) Using components of Eucommia ulmoides extract that are relatively easy to obtain as reducing agents instead of water-soluble high molecular weight aconitic acid, the reducing agent content is higher and the cost is lower.

[0019] (2) Compared with aconitic acid, Eucommia ulmoides extract contains polysaccharides, polyphenols and water-soluble substances. These substances have a better capping and encapsulating effect on nano-copper particles and can effectively prevent the agglomeration of nano-copper particles.

[0020] Compared with other prior arts, the present invention has the following advantages: (1) The nano copper particles prepared by the present invention exhibit excellent dispersibility, have outstanding antioxidant properties, and have extremely uniform particle size distribution, with an average particle size controlled between 3 and 4 nm.

[0021] (2) The nano copper particles prepared in the present invention are used as catalysts, and the catalytic kinetic constants for catalytic reduction of methylene blue (MB) and carmine are 3.03×10 -3 s -1 and 2.17×10 -3 s -1 The amount of nano-copper solution added was 0.3 mL, which was much less than that of the existing technology, but the catalytic activity could reach one-fourth of that of the existing technology. The catalytic kinetic constants of nano-copper particles in the catalytic reduction of 2-nitrophenol (2-NP), 4-nitrophenol (4-NP) and 2,4-dinitrophenol (2,4-DNP) were 2.14×10 -3 s -1 , 2.36×10 -3 s -1 and 1.58×10 -3 s -1 The amount of nano copper solution added was 1 mL, 0.4 mL and 0.2 mL respectively, which is much lower than the existing technology, and the catalytic activity is one-fifth to one-third of the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Transmission electron microscopy image of synthesized nanocopper.

[0023] Figure 2 This is the XRD pattern of synthesized nano-copper.

[0024] Figure 3 This is the FTIR spectrum of synthesized nano-copper.

[0025] Figure 4 This is the UV-visible absorption spectrum of methylene blue (MB) reduction reaction without adding nano-copper catalyst as time increases.

[0026] Figure 5 This is the UV-visible absorption spectrum of the reduction reaction of Carmine without adding nano-copper catalyst as time increases.

[0027] Figure 6 The UV-visible absorption spectrum of methylene blue (MB) reduction reaction with the addition of nano-copper catalyst as time increases.

[0028] Figure 7 This is the UV-visible absorption spectrum of the reduction reaction of carmine with the addition of nano-copper catalyst as time increases.

[0029] Figure 8The kinetic curve of the catalytic reaction of methylene blue (MB) and carmine (Carmine) after adding nano-copper catalyst shows the change of ln(At / A0) over time.

[0030] Fig. 9 This is the UV-visible absorption spectrum of the reduction reaction of 2-nitrophenol (2-NP) with the addition of nano-copper catalyst as time increases.

[0031] Fig.10 This is the UV-visible absorption spectrum of the 4-nitrophenol (4-NP) reduction reaction with the addition of nano-copper catalyst as time increases.

[0032] Fig.11 The UV-visible absorption spectrum of the reduction reaction of 2,4-dinitrophenol (2,4-DNP) with the addition of nano-copper catalyst as time increases.

[0033] Fig.12 The kinetic curve of ln(At / A0) changing with time for the catalytic reaction of 2-nitrophenol (2-NP), 4-nitrophenol (4-NP), and 2,4-dinitrophenol (2,4-DNP) after adding nano-copper catalyst. DETAILED DESCRIPTION Example

[0034] Weigh 2.1387 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80°C and keep it stable.

[0035] Weigh 0.8525 g of cupric chloride dihydrate, dissolve it in 50 mL of deionized water to prepare a 0.1 mol / L aqueous solution, transfer it to a constant pressure funnel by magnetic stirring, fix the constant pressure funnel to the reactor, and evenly add the solution to the reactor; after the addition is complete, start the timing, react for 8 hours, and obtain a yellow-brown stable aqueous solution of nano-copper particles.

[0036] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0037] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0038] pass Figure 1It can be confirmed that the copper nanoparticles Cu NPs prepared by the above method exhibit good dispersibility and the agglomeration phenomenon is effectively controlled; in this preparation process, the Eucommia leaf extract plays a significant role as a dispersant; Figure 2 The comparison results show that the diffraction peaks in the sample are consistent with those in the standard copper PDF card, especially the three diffraction peaks at 41.878°, 49.871°, and 74.024°, which correspond to the (111), (200), and (220) crystal planes, respectively. This further confirms that the prepared sample is a single copper structure. Figure 3 Several characteristic absorption peaks were revealed in the FTIR spectrum, among which the absorption peaks in the wavenumber range of 3700-3100 cm⁻¹ reflected the stretching vibration of the OH bond in Cu NPs and water; and the absorption peaks in the range of 3000-2800 cm⁻¹ were attributed to the CH bond; in addition, the absorption peaks at 1643, 1410, 1342 cm⁻¹ and 1280, 1108, 1016, 842 cm⁻¹ in the spectrum indicated the stretching vibration of the carbonyl group (C=O), aromatic ring C=C, C-OH and CO bond, respectively; these FTIR spectral features indicate that the formation of Cu NPs may be related to the flavonoids and phenolic compounds in the eucommia leaf extract, and these compounds can be adsorbed on the surface of Cu NPs to effectively prevent their agglomeration; therefore, in the preparation process of nanocopper, the chemical components of the eucommia leaf extract not only acted as a reducing agent, but also played the role of a dispersant and stabilizer. Example

[0039] Weigh 2.1387 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80°C and keep it stable.

[0040] Weigh 0.8525 g of cupric chloride dihydrate, dissolve it in 50 mL of deionized water to prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel by magnetic stirring. Fix the constant pressure funnel to the reactor and evenly add the solution to the reactor. After the addition is complete, start the timing and react for 9 hours to obtain a yellow-brown stable aqueous solution of nano-copper particles.

[0041] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0042] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 15 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0043] Example 3: Using the Cu NPs prepared in Example 1 to catalyze the reduction of organic dyes Weigh 0.7566 g of sodium borohydride (NaBH 4 ) in a beaker and dissolved in 200 mL of deionized water to prepare a 0.1 mol / L aqueous solution. Dissolve completely and keep away from light for later use.

[0044] Weigh 2 mg and 5 mg of methylene blue (MB) and carmine, respectively, and dissolve them in 20 mL of deionized water to form 0.3 mmol / L and 0.5 mmol / L solutions to simulate waste liquid, respectively, and seal them for later use.

[0045] Add 40 mL NaBH 4 The solution was added to 9 mL of methylene blue (MB) solution, and 0.3 mL of the nano copper solution prepared in Example 1 was added; 40 mL of NaBH 4 The solution was added to 5 mL of Carmine solution, and 0.1 mL of the prepared nanocopper solution was added; the reaction was carried out at room temperature, water was used as a reference, the ultraviolet light absorption was measured, and the absorbance of the organic dye per minute was recorded.

[0046] The absorbance of the two organic pigment solutions was recorded using an ultraviolet-visible spectrophotometer (UV-Vis, Cary 60, Agilent, US) to analyze their concentration differences. The above experiments were carried out at room temperature.

[0047] The catalytic effect of the nano copper particles prepared in the present invention on the reduction of organic dyes is characterized by catalytic reduction reactions of two organic dyes, methylene blue (MB) and carmine.

[0048] Figure 4 and Figure 5 When no nano-copper catalyst is added, NaBH 4 UV-absorption spectra of methylene blue (MB) and carmine reduction over time; Figure 6 and Figure 7 After adding nano copper catalyst, NaBH 4 UV-absorption spectra of methylene blue (MB) and carmine reduction over time; Figure 8 This is the decomposition curve of two organic dyes when nano copper is added.

[0049] Methylene blue (MB) and carmine have strong UV absorption peaks at 664 nm and 507 nm, respectively. Figure 4 and Figure 5 When no nano-copper catalyst is added, NaBH 4The UV-absorption spectra of the reduction of methylene blue (MB) and carmine vary with time. The spectra show that the reduction rates of the two dyes are very slow. Figure 6 and Figure 7 It was found that after adding nano-copper, the ultraviolet absorption peaks of the two dyes almost dropped to 0 in a very short time, indicating that the two dyes were catalytically reduced to substances with little pollution; therefore, the nano-copper prepared by the present invention has a good effect on NaBH 4 Reduced methylene blue (MB) and carmine both have good catalytic effects; Figure 8 The catalytic kinetic curves of the two dyes show that there is a linear relationship between ln (At / A0) and reaction time, reflecting the specific effect of nano-copper on the catalytic reduction of dyes.

[0050] Example 4: Using the Cu NPs prepared in Example 1 to catalyze the reduction of nitrophenol Weigh 1.1349 g NaBH 4 Put it in a beaker and dissolve it in 300 mL of deionized water to prepare a 0.1 mol / L aqueous solution. Dissolve it completely and keep it away from light for later use.

[0051] Weigh 15 mg, 5 mg and 3 mg of 2-nitrophenol (2-NP), 4-nitrophenol (4-NP) and 2,4-dinitrophenol (2,4-DNP), respectively, dissolve in 10 mL of deionized water to prepare 10 mmol / L, 4 mmol / L and 2 mmol / L solutions, seal and protect from light for later use.

[0052] Add 80 mL NaBH 4 The solution was added to 2 mL of 2-nitrophenol (2-NP) solution, and 1 mL of the nano copper solution prepared in Example 1 was added; 80 mL of NaBH 4 The solution was added to 2 mL of 4-nitrophenol (4-NP) solution, and 0.4 mL of the prepared nanocopper solution was added; 80 mL of NaBH 4 The solution was added to 2 mL of 2,4-dinitrophenol (2,4-DNP) solution, and 0.2 mL of the prepared nanocopper solution was added. The reaction was allowed to proceed at room temperature. Water was used as a reference. The ultraviolet light absorption was measured, and the absorbance of the three nitrophenols per minute was recorded.

[0053] The absorbance of the three nitrophenol solutions was recorded by UV-Vis spectrophotometer (Cary 60, Agilent, US) to analyze their concentration differences. The above experiments were carried out at room temperature.

[0054] The catalytic effect of the nano copper particles prepared in the present invention on the reduction of organic dyes is characterized by catalytic reactions on three nitrophenols. Fig. 9 , Fig.10 and Fig.11 These are the spectra of UV-absorption changing with time when 2-nitrophenol (2-NP), 4-nitrophenol (4-NP) and 2,4-dinitrophenol (2,4-DNP) are catalytically reduced with the addition of nano-copper; Fig.12 This is the decomposition curve of three nitrophenols when nano copper is added.

[0055] pass Fig. 9 , Fig.10 and Fig.11 It was found that after adding nano copper, the ultraviolet absorption peaks of the three nitrophenols also dropped to 0 in a short time. Therefore, the nano copper prepared by the present invention has a good catalytic reduction effect on the three nitrophenols. Fig.12 is the catalytic kinetic curve. It can be seen that there is a linear relationship between ln (At / A0) and reaction time, reflecting the specific effect of nano-copper on the catalytic reduction of nitrophenol.

[0056] Comparative Example 1: Weigh 3.4219 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80 °C and keep it stable.

[0057] Weigh 0.8525 g of copper chloride dihydrate, dissolve it in 50 mL of deionized water, prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel by magnetic stirring. Fix the constant pressure funnel to the reactor and drip the solution evenly into the reactor. After the dripping is complete, start the timing and react for 8 hours to obtain a yellow-brown stable aqueous solution of nano copper particles.

[0058] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0059] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0060] According to the requirements of Example 3, taking methylene blue (MB) as an example, the catalytic rate constant of the prepared nano-copper catalyst for methylene blue (MB) is 3.11×10 -3 s -1, there is no obvious improvement compared with Example 1, and the experiment used more Eucommia ulmoides extract, which increased the experimental cost.

[0061] Comparative Example 2: Weigh 4.2625 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80 °C and keep it stable.

[0062] Weigh 0.8525 g of copper chloride dihydrate, dissolve it in 50 mL of deionized water, prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel by magnetic stirring. Fix the constant pressure funnel to the reactor and drip the solution evenly into the reactor. After the dripping is complete, start the timing and react for 8 hours to obtain a yellow-brown stable aqueous solution of nano copper particles.

[0063] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0064] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0065] According to the requirements of Example 3, taking methylene blue (MB) as an example, the catalytic rate constant of the prepared nano-copper catalyst for methylene blue (MB) is 3.56×10 -3 s -1 , there is no obvious improvement compared with Example 1, and the experiment used more Eucommia ulmoides extract, which increased the experimental cost.

[0066] Comparative Example 3: Weigh 0.8525 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80 °C and keep it stable.

[0067] Weigh 0.8525 g of copper chloride dihydrate, dissolve it in 50 mL of deionized water, prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel by magnetic stirring. Fix the constant pressure funnel to the reactor and drip the solution evenly into the reactor. After the dripping is complete, start the timing and react for 8 hours to obtain a yellow-brown stable aqueous solution of nano copper particles.

[0068] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0069] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0070] According to the requirements of Example 3, taking methylene blue (MB) as an example, the catalytic rate constant of the prepared nano-copper catalyst for methylene blue (MB) is 2.09×10 -3 s -1 Compared with Example 1, although the usage of Eucommia ulmoides extract was reduced to a large extent, the catalytic effect was significantly reduced.

[0071] Comparative Example 4: Weigh 2.1387 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 80°C and keep it stable.

[0072] Weigh 0.8525 g of copper chloride dihydrate, dissolve it in 50 mL of deionized water, prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel under magnetic stirring. Fix the constant pressure funnel to the reactor and drip the solution evenly into the reactor. After the dripping is complete, start the timing and react for 6 hours to obtain a yellow-brown stable aqueous solution of nano copper particles.

[0073] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0074] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0075] According to the requirements of Example 3, taking methylene blue (MB) as an example, the catalytic rate constant of the prepared nano-copper catalyst for methylene blue (MB) is 1.96×10 -3 s -1 Compared with Example 1, the reaction time of the Eucommia ulmoides extract and cupric chloride dihydrate was shortened, but the catalytic effect was significantly reduced.

[0076] Comparative Example 5: Weigh 2.1387 g of Eucommia ulmoides extract and dissolve it in 50 mL of deionized water. Stir it evenly with a magnetic stirrer. Add the mixture into a reactor and heat it to 70°C and keep it stable.

[0077] Weigh 0.8525 g of copper chloride dihydrate, dissolve it in 50 mL of deionized water, prepare a 0.1 mol / L aqueous solution, and transfer it to a constant pressure funnel by magnetic stirring. Fix the constant pressure funnel to the reactor and drip the solution evenly into the reactor. After the dripping is complete, start the timing and react for 8 hours to obtain a yellow-brown stable aqueous solution of nano copper particles.

[0078] The obtained aqueous solution of nano-copper particles was slowly poured into a dialysis bag with a molecular weight of 300, and the dialysis bag was placed in a beaker filled with deionized water for dialysis. Rapid dialysis was sufficient to obtain an aqueous solution of nano-copper particles with less impurities.

[0079] After the dialysis, the nano-copper particle aqueous solution with less impurities was centrifuged at 8000 rpm for 10 minutes to remove the oxidized nano-copper precipitate, and the upper clear liquid was taken to obtain a pure nano-copper particle aqueous solution.

[0080] According to the requirements of Example 3, taking methylene blue (MB) as an example, the catalytic rate constant of the prepared nano-copper catalyst for methylene blue (MB) is 1.96×10 -3 s -1 Compared with Example 1, the hydration reaction temperature of the Eucommia ulmoides extract was lowered and the catalytic effect was significantly reduced.

[0081] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing nano copper particles from Eucommia ulmoides extract, characterized in that: The method comprises the following steps: dissolving an eucommia extract in water to form an aqueous solution, heating the aqueous solution to 70-80°C, and magnetically stirring the aqueous solution until it is fully mixed; when the solution reaches a stable state, the divalent copper salt solution is slowly added to the solution while maintaining stirring, and the reaction is continued for 6-9 hours to reduce copper ions, thereby obtaining a yellow-brown aqueous solution containing nano-copper particles; the solution is then dialyzed to remove impurities, and further purified by centrifugal separation, and the supernatant is taken to finally obtain a pure nano-copper aqueous solution.

2. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: The mass ratio of the eucommia extract to the copper solution is (1-5):

1.

3. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: The solution concentration of Eucommia ulmoides extract is 0.04 g / mL~0.1 g / mL.

4. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: The divalent copper salt solution is a cupric chloride solution, and the concentration of the cupric chloride solution is 0.01 g / mL~0.02 g / mL.

5. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: When adding the divalent copper salt solution, add it slowly through a constant pressure funnel and keep it away from light.

6. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: The molecular weight cutoff of the dialysis bag used for dialysis treatment is greater than 300, and the dialysis time is 6 to 12 hours.

7. The method for preparing nano copper particles from Eucommia ulmoides extract according to claim 1, characterized in that: The centrifugal separation speed is 7000~8000 rpm and the centrifugal time is 10~15 min.

8. Use of the nano copper particles obtained according to the preparation method according to any one of claims 1 to 7 in catalytic reduction reactions.

Citation Information

Patent Citations

  • Surface finish nano copper / copper alloy particles and preparation thereof

    CN101259531A

  • Preparation method of nano-copper

    CN101607317A

  • Method for preparing nano-copper

    CN101890506A

  • Preparation method for antioxidant copper nanopowder

    CN105945302A

  • Preparation method of nano-copper particles with ultra-small particle size

    CN109807351A

Cited By

  • Method for green synthesis of nano-copper by using black rice extracting solution and application of nano-copper

    CN119733845A